2009
DOI: 10.1111/j.1532-950x.2009.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Feline Ilial Fractures: A Prospective Study of Dorsal Plating and Comparison with Lateral Plating

Abstract: Dorsal plating of feline iliac fractures may reduce complications associated with pelvic canal narrowing such as constipation and megacolon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 13 publications
3
43
2
Order By: Relevance
“…In a recent study in cats it was demonstrated that screws have less than 80% bone purchase per unit length of ilium compared to dogs . Poor screw bone purchase may explain the high rate of screw loosening in lateral plating of the feline ilium …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study in cats it was demonstrated that screws have less than 80% bone purchase per unit length of ilium compared to dogs . Poor screw bone purchase may explain the high rate of screw loosening in lateral plating of the feline ilium …”
Section: Discussionmentioning
confidence: 99%
“…Techniques for the repair of ilial fractures in cats include intramedullary pinning, pin and wire combination, screw and wire combination, plate and pin combination, and lateral as well as dorsal plating. Lateral plating is the most frequently reported method . A recent study evaluating cuttable plates and dynamic compression plates for lateral plating in 21 cats reported a high frequency of screw loosening (62%) and potential loss of fixation associated with more severe pelvic canal narrowing.…”
mentioning
confidence: 99%
“…Additionally, mean pelvic canal narrowing, assessed by comparing width of the pelvic canal between the acetabulae and cranial sacral width was measured on 6‐ or 8‐week postoperative radiographs. Mean decrease in pelvic canal width was 11% (range, 0–33%) between immediate postoperative and recheck radiographs . This was significantly less than the mean of 25% (5–60%) pelvic canal narrowing reported for a laterally plated group of cats with data published in a companion report .…”
mentioning
confidence: 57%
“…However, approaches not tested in this study can be considered when treating such fractures (Langley-Hobbs et al, 2009;Krebs et al, 2014).…”
Section: Discussionmentioning
confidence: 99%